Persepsi Petani tentang Program Asuransi Usaha Tani Padi (AUTP) di Kota Padang - Melani, Zaskhia; Mutiara, Vonny Indah; Paloma, Cindy (Universitas Medan Area, 2025)
Padang City is one of the highest rice production areas in West Sumatra Province. However, there are significant risks and uncertainty in conducting rice cultivation including climate change, as well as being subject to pests and diseases of crops and livestock, and the fluctuation of rice prices in the market. Agricultural risk mitigation is a solution to dealing with high levels of risk. The Government has made efforts to mitigate agricultural risks through the Rice Farming Business Insurance (AUTP) program. Therefore, this study aims to analyse farmers' perceptions of the AUTP program in Padang City. The research method used is survey. Primary data were collected using a structured interviews for 100 respondents in three subdistricts. Respondents were selected by using non probability sampling with a purposive sampling method. The study results show that most of respondents already knew about the AUTP program from Extension Officers. However, almost 82 percent of respondents have never claimed due to the high percentage of damage claims (75% of the total affected land) which should be full filed. Farmers’ reason for join the AUTP program is because of they had experienced crop failure. Though, they are willing to pay AUTP premiums of IDR 36,000/Ha per planting season as a protection for their rice farming businesses.